АЛЛОКСАН ДИАБЕТІНЕ ШАЛДЫҚҚАН ЕГЕУҚҰЙРЫҚТАРДЫҢ АНТИОКСИДАНТТАРМЕН ТҮЗЕТУЛЕРДЕН КЕЙІНГІ ҚАН ПЛАЗМАСЫНЫҢ БИОХИМИЯЛЫҚ КӨРСЕТКІШТЕРІНІҢ ЕРЕКШЕЛІКТЕРІ (Experimental biology, 2015)
The use of a complex of soya milk and α - tocopherol preliminary and against formation alloxan a diabetes promoted normalization of level of glucose in blood, urine and insulin level, to preservation of initial weight of a body of animals though completely control values it was not reached.
Keywords: soya milk; α – tocopherol